2021
DOI: 10.1097/md.0000000000025315
|View full text |Cite
|
Sign up to set email alerts
|

Association between programmed cell death ligand 1 expression and thyroid cancer

Abstract: Background: Programmed cell death ligand 1 (PD-L1), which is highly expressed in a variety of malignant tumors, is closely related to clinicopathological features and prognosis. However, there are few studies on the potential effects of PD-L1 on thyroid carcinoma, the incidence of which has shown an upward trend worldwide. This study aimed to explore the association between PD-L1 expression and clinicopathological features and prognosis of thyroid cancer. Methods: An el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(44 reference statements)
0
8
0
1
Order By: Relevance
“…Several experimental and clinical data suggest that other molecules may have a role in the prognostic stratification of TC patients. These include immune checkpoint factors and immune-related signature (IRS), estrogen receptors, Vitamin D, tumor angiogenic microenvironment, circular RNAs, long noncoding RNAs, and the angiotensin converting enzymes ACE and ACE2 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. However, all of them are awaiting validation in large case studies.…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
“…Several experimental and clinical data suggest that other molecules may have a role in the prognostic stratification of TC patients. These include immune checkpoint factors and immune-related signature (IRS), estrogen receptors, Vitamin D, tumor angiogenic microenvironment, circular RNAs, long noncoding RNAs, and the angiotensin converting enzymes ACE and ACE2 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. However, all of them are awaiting validation in large case studies.…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
“…In meta‐analysis of 906 non‐medullary thyroid carcinomas, PD‐L1 positivity was significantly associated with concurrent thyroiditis with odds ratio (OR) 1.65 [19]. In another meta‐analysis, concurrent chronic lymphocytic thyroiditis was shown to be associated with PD‐L1 positivity with OR 2.19 (p = 0.479) [21] and HR = 1.41 (p = 0.007) [20]. Furthermore, both PD‐L1 and PD‐1 positivity in PTC were shown to correlate with chronic lymphocytic thyroiditis [22].…”
Section: Discussionmentioning
confidence: 99%
“…In systematic reviews and meta-analyses, PD-L1 expression in non-medullary thyroid carcinomas showed significant association with poor survival and recurrence, tumor size, extrathyroidal extension, and unifocality [19,20]. Nevertheless, the comparison of various studies faced the inconsistencies between used antibodies, staining procedures and platforms, as well as scoring methods and cutoffs [19,21].…”
mentioning
confidence: 99%
“…Based on meta-analysis by Wan et al, 28 they found that high expression of PD-L1 in patients with thyroid cancer was associated with poor DFS (disease free survival), tumour size ≥2 cm, tumour recurrence, extrathyroidal extension, concurrent thyroiditis, unifocal tumour, and absence of psammoma bodies. Some of this clinicopathological variables can be also found in our study, such as tumor size and extrathyroidal extension.…”
Section: Discussionmentioning
confidence: 99%